2000
DOI: 10.1093/jn/130.9.2256
|View full text |Cite
|
Sign up to set email alerts
|

Living Arrangements Affect Dietary Quality for U.S. Adults Aged 50 Years and Older: NHANES III 1988–1994

Abstract: The number and proportion of older U.S. adults who live alone have increased dramatically in the past three decades, and there is concern that these individuals may have particularly poor dietary quality. We examined the association of four living arrangements (living with a spouse only, with a spouse plus someone else, with someone other than a spouse or living alone) with dietary quality (the number of low nutrients out of a possible 15, with low defined as <67% of the recommended dietary allowance) among 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 17 publications
7
53
1
2
Order By: Relevance
“…It has been reported previously that married individuals tend to eat a greater number of meals and have higher energy intakes (23). These results from our study and previous studies (23) may be a reason for the increased weight gain among married individuals as reported in the literature (40).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It has been reported previously that married individuals tend to eat a greater number of meals and have higher energy intakes (23). These results from our study and previous studies (23) may be a reason for the increased weight gain among married individuals as reported in the literature (40).…”
Section: Discussionsupporting
confidence: 86%
“…It has been noted that intake of fast foods, snacks (5,6), and sweetened beverages (5) has increased among young adults, whereas intake of fruits, vegetables (7), and dairy products (6) has decreased. Various factors such as socioeconomic status (eg, income and/or education) (8)(9)(10)(11)(12)(13)(14)(15)(16), demographics (eg, sex and ethnicity) (17)(18)(19), and lifestyle characteristics (eg, marital status [20][21][22][23] and physical activity [15,24,25]) have been thought to influence the food choices in this age group. However, the majority of studies conducted in the United States have either examined cost issues with respect to purchasing specific healthful foods (14,(26)(27)(28)(29) or have examined the influence of socioeconomic status on nutrient intakes (30,31) rather than the consumption of specific food groups.…”
mentioning
confidence: 99%
“…Based on Indonesia's Basic Health Research in 2013, the percentage of women living alone who routinely perform strenuous activities (such as sports) is 25.46 per cent, lower than women who live with a non-spouse (26.34 per cent). This result contrasts with the research of Davis et al (2000) which found the women who live with a non-spouse exercise less than those living alone (Table 1).…”
Section: Resultscontrasting
confidence: 93%
“…This is because women who live alone are more likely to have higher education (12.62 per cent) and to work (65.77 per cent) than those living with others (7.89 per cent; 33.82 per cent), and thus they require a higher energy intake (Davis et al, 2000) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation